Critical delay factors in power transmission projects: a structural equation modeling approach. Issue 6 (26th April 2022) - Pall, Goutom K.; Bridge, Adrian J.; Washington, Simon; Gray, Jason; Skitmore, Martin
Abstract: Power transmission (PT) projects, as an essential link between power generation and distribution, play a vital role in the development of a country. To develop a clear understanding and identification of the critical idiosyncratic causes of delays in PT projects, for the first time, a model is developed to reflect the collective effects of 46 indicators under 10 factors. Based on the extended literature review and 18 sector experts' recommendations, this study introduces two new factors – (i) a sector-specific factor (SSF) and (ii) a general factor (GF), where SSF pertains the uniqueness of PT project delay characteristics and GF drives a less biased data sample. Structural equation modeling (SEM) is used to test and validate the hypothesized model based on 311 valid questionnaire surveys. The validated model establishes SSF and GF as the most critical factors in PT project delays. With the clear insights provided by these findings, this study is expected to have a substantial influence on professionals in minimizing PT and other linear (power and non-power) project time overruns worldwide.